Manejo cultural, relações lineares e plano experimental para girassol - Pereira, Anderson Crestani (2024)
In plant breeding studies of sunflower crops, knowledge of the relationships between crop traits is of great importance. However, the information available in the scientific literature is based on few cultivation environments. Knowledge of the sample size for character evaluation is also of great importance, because if the sample size is smaller than adequate, the estimates obtained will be inaccurate. However, the sample sizes used to evaluate sunflower traits in articles available in the scientific literature are discrepant. Plant density is one of the main agronomic practices that interferes with sunflower grain productivity. However, there is a lack of recommendations on the appropriate sowing density for sunflower grown in second-season conditions. The objective of this research was to evaluate the linear relationships between sunflower traits and identify traits that can assist in the indirect selection of genotypes. Furthermore, the effect of sunflower sowing density on morphological and productive traits of the crop and on the linear relationships between these traits in second-season conditions was evaluated. Finally, to verify the variability of the sample size among sunflower genotypes and estimate the adequate sample size for evaluating the morphological and productive characteristics of the crop. For the first and third chapters, data from five experimental years conducted annually between 2017/2018 and 2022/2023 were used. The experiments were conducted at the Federal University of Santa Maria (UFSM). The experimental design was randomized blocks with four replications, the treatments were characterized by different genotypes, hybrids and cultivars, totaling 34 treatments and 1754 evaluated plants in the five experiments. For the second chapter, data from an experiment conducted in 2022, under second harvest conditions, at the Federal University of Santa Maria (UFSM) were used, adopting the randomized block experimental design, with four replications and six treatments, composed of different sunflower sowing densities. The number of achenes per chapter and the mass of a thousand achenes have a direct effect on the productivity of achenes per plant. The diameter of the capitulum has a direct effect on the number of achenes per capitulum and can be used for indirect selection of sunflower genotypes and cultivars. The sowing density influences the diameter of the capitulum, the number of achenes per capitulum, the individual productivity per plant and the productivity of the plot. The recommended sowing density for second crop conditions is 51.45 thousand plants per hectare. The sowing density influences the magnitude and direction of the linear associations between the traits tested. There is variability in the sample size estimate regarding the variable considered and among genotypes regarding plant height, capitulum diameter, number of achenes per capitulum and individual productivity per plant. The sample size to be evaluated per experimental unit for evaluating the traits plant height and chapter diameter is five plants and 14 plants for the traits number of achenes per chapter and individual productivity per plant.